Glycosylated Haemoglobin (HbA(1)c) - A Marker of Circulating Lipids in Type 2 Diabetic Patients - K., Prabhavathi (JCDR Research and Publications (P) Limited, 2014)
Background: Diabetic patients with concomitant dyslipidemia are often soft targets for cardiovascular disease and deaths. An early intervention to normalize circulating lipids has been shown to reduce cardiovascular morbidity and mortality. Glycosylated hemoglobin (HbA(1)c) is routinely used as a marker to indicate long-term glycemic control. Aim: Our aim was to test whether HbA(1)c can serve as a marker of circulating lipids among Type 2 diabetic patients. Methods: The sera of 130 Type 2 diabetic patients was analyzed for fasting blood sugar (FBS), HbA(1)c and lipid profile consisting of total cholesterol (TC), triglycerides (TG), High-density Lipoprotein (HDL) cholesterol and LDL cholesterol. We divided the subjects based on their glycemic index into three groups; HbA(1)c< 6% as good, HbA(1)c>6% - <9% as poor and HbA(1)c>9% as worst glycemic control. One–way analysis of variance (ANOVA) and post-hoc Dunnett’s multiple comparison tests was used to examine the significance levels for various biochemical parameters in age-categorized groups. Results: The mean ± SD levels of HbA(1)c was significantly higher in females (8.598 ± 2.284 %) compared to males (7.323±2.18 %). Older patients had HbA(1)c, FBS and lipid profile levels similar to younger ones. HbA(1)c showed direct and significant correlations with cholesterol, TG and LDL. Univariate analysis showed that HbA(1)c was a good predictor of circulating lipid levels. Conclusion: The study indicates the usefulness of HbA(1)c as a marker for lipid profile for screening of diabetic patients at high risk of developing cardiovascular diseases.